Impact of general anesthesia on posterior circulation large vessel occlusions after endovascular thrombectomy. Issue 7 (October 2021) - Terceño, Mikel; Silva, Yolanda; Bashir, Saima; Vera-Monge, Víctor A; Cardona, Pere; Molina, Carlos; Chamorro, Ángel; de la Ossa, Natalia P; Hernández-Pérez, María; Werner, Mariano; Camps-Renom, Pol; Rodríguez-Campello, Ana; et al.
Background: The impact of general anesthesia on functional outcome in patients with large vessel occlusion remains unclear. Most studies have focused on anterior circulation large vessel occlusion; however, little is known about the effect of general anesthesia in patients with posterior circulation—large vessel occlusion. Methods: We performed a retrospective analysis from the prospective CICAT registry. All patients with posterior circulation—large vessel occlusion—and undergoing endovascular therapy between January 2016 and January 2020 were included. Demographics, baseline characteristics, procedural data, and anesthesia modality (general anesthesia or conscious sedation) were evaluated. The primary outcome was the proportion of patients with good clinical outcome (modified Rankin Scale score of 0–2) at three months. Results: 298 patients underwent endovascular treatment with posterior circulation—large vessel occlusion—were included. Age, diabetes mellitus, renal insufficiency, baseline National Institutes of Health Stroke Scale score, puncture to recanalization length, ≥3 device passes, absent of successful recanalization (defined as treatment in cerebral ischemia of 3), and general anesthesia were statistically associated with poor outcome (mRS: 3-6). In the multivariable regression, general anesthesia and ≥3 device passes were independently associated with poor outcome (aOR: 3.11, (95% CI: 1.34–7.2); P  = 0.01 and 3.77, (95% CI: 1.29–11.01); P  = 0.02, respectively). Patients treated with general anesthesia were less likely to have a good outcome at three months compared to conscious sedation (19.7% vs. 45.1%, P  < 0.001). Conclusions: In our study population, general anesthesia use is associated with poor clinical outcome in patients with posterior circulation—large vessel occlusion—treated endovascularly.